Women and Agribusiness - Barrientos, Stephanie. author. aut Link
XVII, 231 p.
Keywords: Fresh fruit exported from Chile has become commonplace in our supermarkets during the winter months. Women form a large part of the seasonal labour force in this branch of Chilean agribusiness. This book provides an in-depth examination of the 'fruit explosion' in Chile, and the implications for rural women of working in agribusiness. It examines state policies to support seasonal workers, and asks whether supermarket codes of conduct will benefit these workers in the context of a global economy.